Perspectives on Odor-Based Control of Tsetse Flies in Africa - Mireji, Paul O.; Mang’era, Clarence M.; Bwana, Billiah K.; Hassanali, Ahmed (Frontiers in Physiology, 2022)
Tsetse transmitted trypanosomiases are among the most neglected human and animal tropical diseases in sub-Sahara Africa, with devastating health and economic consequences. Although all tsetse species are susceptible to trypanosome infections, their differential attraction and feeding preferences for different wildlife, domestic animals and humans constitute critical determinants of the species of trypanosomes they predominantly transmit. Artificial bait technologies, based on long-range tsetse olfactory responses to natural cues emitted by preferred hosts and blends of synthetic versions that mimic these cues, have successfully been applied in attraction (‘pull’ tactic) and reduction of populations of some species in the field. On the other hand, the olfactory attribute associated with active avoidance of tsetse-refractory non-hosts, has also been exploited in design of blends of tsetse repellents for livestock protection (‘push’ tactic). These have opened possibility of spatially strategic deployment of the two sets of odor baits in ‘push-pull’ tactics. A recent study explored possibility of developing blends with enhanced attraction and repellence compared with those associated with savannah tsetse hosts and non-hosts, respectively. The studies evaluated structure-activity and blends of different components, which generated two novel blends. One based on attractive constituents associated with buffalo (Syncerus caffer) comprised of ε-nonalactone, nonanoic acid, 2-nonanone (in 1:3:2 proportion) delivered together with acetone, which showed significantly better attractancy on savannah tsetse than the standard blend comprised of 3-propylphenol, octenol, p-cresol and acetone (POCA). The other blend comprised of δ-nonalactone, heptanoic acid, 4-methylguaiacol and geranylacetone (in 6:4:2:1 proportion was significantly more repellent than previously characterized blend based on tsetse refractory waterbuck (Kobus defassa) constituents (δ-octalactone, pentanoic acid, guaiacol geranylacetone). So far, no effective attractants or repellents of riverine tsetse species have been characterized. Optimized attractant and repellent blends for savannah tsetse flies lay down useful groundwork for the future development of the ‘push-pull’ deployment tactic for area-wide control of tsetse flies.